(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The basic objective of governance is all round welfare of the citizens. While one aspect of governance relates to safeguarding the legal rights of all citizens, an equally important aspect is concerned with ensuring equitable access to public services and the benefits of economic growth to all. E-governance can enable the government to discharge its functions more effectively. However, this requires the government to change itself, its process, its outlook, laws, rules and regulations and also its way of interacting with the citizens. It also requires capacity building within the government and creation of general awareness about e-governance among the citizens. Thus, e-Governance is basically associated with carrying out the functions and achieving the results of governance through the utilization of what has today come to be known as ICT (Information and communications Technology). The reason why the nations around the world are increasingly adopting for e-governance is that governance has become more complex and varied in the last few decades and more importantly, citizens’ expectations from government have increased manifold. ICT facilitates efficient storing and data retrieval of data, instantaneous transmission of information, processing information and data faster than the earlier manual systems, speeding up governmental processes, taking decisions expeditiously and judiciously, increasing transparency and enforcing accountability.[1] It also helps in increasing the reach of government both geographically and demographically.E-governance can transform the existing government system and consolidate the establishment of an inclusive governance system through digital means that is capable of experiencing its powers and functions more efficiently and effectively. It can pave the way for a governance system that is committed to working with civil society in a transparent and accountable way to reduce poverty, safeguard the environment, redress inequality, foster security and fulfill social, economic, cultural, civic and political rights. E-government supports broad public sector reforms and good governance through the introduction of innovative and sustainable applications ICT both within government administrations as well as in their interaction with citizens and the private sector.[2]